Bauhinia affinis (Fabaceae) : una nueva cita para la flora argentina - Fortunato, Renee Hersilia (Instituto de Botánica Darwinion, 2019)
Bauhinia affinis Vogel is reported for the first time in the NE extreme of Argentina. The number of species of the genus recorded for the country is increased to 7. The species is described and illustrated indicating ist geographic distribution; its affinities with the related species are discussed and a diagnostic key for its identification in Argentine flora is included.